Longitudinal Taphonomic Studies of Mammal Carcasses from the Rio Salado Valley, Mendoza, Argentina - Clara Otaola; Alfonsina Tripaldi (Ethnobiology Letters, 2016)
Taphonomic studies aid in understanding the transition of organic matter from living contexts (the biosphere) to geological contexts (the lithosphere), and how agents and processes affect skeletal remains in the archaeological record. Archaeological research in the Atuel River valley, Mendoza, Argentina, has been carried out for several years. However, actualistic approaches to examine local and regional taphonomic processes have only been recently developed in this area. Longitudinal studies of disarticulation and dispersion of bones from carcasses are presented here in order to understand how skeletal materials are naturally added to, subtracted from, and mixed within the archaeological record. In this paper we explore variability in the influence of taphonomic processes in different microhabitats of the valley and how these mechanisms impact the potential of mixing during bone deposition in the archaeological record. There are some qualitative differences between carcasses deposited in different landforms, showing that each place has its own taphonomic history, principally influenced by the geomorphic and ecologic processes that operate in different landforms.